Valoración de la harina de banano musa sapientum según sus grados de cosecha en las variedades valery cavendish gigante y filipino - Carbay Uyaguari, Edwin Efrén (2014)
In this research work, banana (Musa sapientum) flour was assessed according to their harvest grades in varieties Valery, Filipino and Giant Cavendish. Banana flour was elaborated using bananas from the three varieties, and each group of harvest grade, using an already established methodology. Some of the parameters for this assessment are bromatologia analyzes which comprises analyzes of proteins, fats, pH, moisture, ash, carbohydrates, vitamins, minerals such as potassium, calcium, iron, phosphorus. Most of the analyzes are not significant when compared to the other banana varieties, but when compared to wheat flour we realize that there is a great significance in the values obtained, the most notorious result came from the proteins analysis, because we see that the banana flour that contains the highest percentage of proteins, Giant Cavendish with 3.87%, is much lower than wheat flour which has a 9.10%. This gives us a difference of 5.23% of proteins, another analysis it should be paid attention to is fat, because banana flour has a lower rate of 3%, this make that is located in lower concentration, and color of the foods traffic light is green, and this is good according to the current health regulations for food labeling in Ecuador. While mineralogical analysis gives different results between the flours, the most notorious analysis is potassium, banana flour lower percentage comes from the variety Filipino with an amount of 1.42%, but flour wheat contains an amount of 0.17% potassium, this gives us a difference of 1.25% which indicates that banana flour provides a great contribution to potassium nutrition. In analyzes of microbiological load, banana flour and wheat flour are within the INEN required parameters to commercialize flour. Converting fresh bananas to banana flour results indicated that there is statistical significance between groups of harvest grade and variety, which gives us the highest conversion is the variety Valery with the harvest grades 41-44 we had a value of 6.51, but the best conversion comes from the variety Filipino with the harvest grades of 45-48, gives us a value of 5.85, which indicates that we need only 5.85 kilograms of bananas for 1 Kilogram of banana flour, the lower is the most favorable for the production of flour conversion. The price for banana flour was obtained according to their harvest grades and varieties, this gave us the highest value for the group Giant Cavendish with harvest grades of 45-48 and with a value of $ 1.46 a kilogram of banana flour, value more expensive variety was Valery, it gave the group level of harvest 41-44 with a value of $ 2.61 a kilogram, to get the retail price the average of all values was obtained, this gave us the $ 1.99 kilograms of banana flour, note that the price obtained only considered production costs without taking the balance of the investment, plus these prices were obtained in laboratory conditions, but they can lower these values using industrial machines to improve production of flour.